2022
DOI: 10.1093/infdis/jiac196
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Signature of Subclinical Coronary Artery Disease in People With HIV: Analysis of the REPRIEVE Mechanistic Substudy

Abstract: Background People with HIV (PWH) have subclinical coronary artery disease (CAD) despite low traditional atherosclerotic cardiovascular disease (ASCVD) risk scores. Coronary plaque in PWH presents as a unique phenotype, but little is known about the contributions of specific inflammatory pathways to plaque phenotypes in PWH. Methods The REPRIEVE Mechanistic Substudy enrolled PWH on ART without known cardiovascular disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…CCL23, SLAMF1 and MCP-1 are involved in monocyte activation, which could lead to sustained inflammation among PWH 6,12 and were suggested to be involved in the pathogensis of several age-related diseases, such as cardiovascular diseases (CVD) 20 , chronic kidney disease 21 , rheumatoid arthritis and atopic dermatitis 6,22,23 . CCL23 was shown to be positively associated with the presence of coronary plaque among PWH 24 , and genetic variants in the SLAMF1 gene that regulate the abundance of SLAMF1 protein were associated with memory decline 25 . MMP-1 functions primarily to degrade several types of collagens and plays an important role in skin aging 26 .…”
Section: Discussionmentioning
confidence: 99%
“…CCL23, SLAMF1 and MCP-1 are involved in monocyte activation, which could lead to sustained inflammation among PWH 6,12 and were suggested to be involved in the pathogensis of several age-related diseases, such as cardiovascular diseases (CVD) 20 , chronic kidney disease 21 , rheumatoid arthritis and atopic dermatitis 6,22,23 . CCL23 was shown to be positively associated with the presence of coronary plaque among PWH 24 , and genetic variants in the SLAMF1 gene that regulate the abundance of SLAMF1 protein were associated with memory decline 25 . MMP-1 functions primarily to degrade several types of collagens and plays an important role in skin aging 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the relation of these proteins with the pathophysiology ( Cai et al., 2014 ; Kubin et al., 2011 ) and the incidence of CVD ( Bell et al., 2016 , 2018 ; Bielinski et al., 2017 ; Ferreira et al., 2019 ; Gruson et al., 2017 ; Ikeda et al., 2021 ; Ix Joachim et al., 2012 ; Paul et al., 2021 ; Vázquez-Sánchez et al., 2021 ) in the general population and PLHIV ( Atta et al., 2016 ; Domingo et al., 2015 ; García-Broncano et al., 2014 ). In addition, OSM receptor has been reported to be associated with the presence of coronary calcium, independent from traditional atherosclerotic CVD risk, in PLHIV on ART ( Kolossváry et al., 2022 ). Collectively, these findings support previous reports that increased inflammation may follow or induce non-AIDS comorbidities, and further pinpoint PD-L1, VEGFA, LAP TGFβ-1, and TNFRSF9 as possible targets to decrease the risk for malignancies in well-treated PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have noted altered immune activation and inflammatory indices in PWH; the excess in CV events has been attributed to this alternative mechanistic pathway independent of traditional risk factors [20,39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have noted altered immune activation and inflammatory indices in PWH; the excess in CV events has been attributed to this alternative mechanistic pathway independent of traditional risk factors [ 20 , 39 ]. As with the relationships noted between CVH and events and atherosclerosis, two studies in the general population have also found relationships between poor CVH and a variety of biomarkers including higher PAI-1, aldosterone, hs-CRP, D-dimer, fibrinogen, homocysteine, GDF-15, hs-troponin T, IL-6 and GlycA, and lower levels of NT-proBNP [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%